Interfacial electrochemistry - Schmickler, Wolfgang (Oxford University Press, 1996)
This book provides an advanced level introduction to the electrochemistry. It provides the background required to follow current research in a subject which has again become highly topical through the recent development of surface sensitive techniques. It is divided into three parts covering the fundamentals of the subject, the experimental methods including surface sensitive techniques, and a few important problems in theoretical electrochemistry. A special chapter is devoted to liquid-liquid interfaces which have become of interest because of their relation to biological membranes.